Pospay sebagai Alat Transaksi Pembayaran di Era Digital Perusahaan PT. Pos Indonesia (PERSERO) Regional V Surabaya - Risos Valvenchia; Dhani Ichsanuddin Nur (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Abstract. The advancement of information and communication technology in the digital era has driven transformation across various sectors, including financial services. PT Pos Indonesia has responded to these changes by launching POSPAY, a digital payment platform that facilitates various transactions such as bill payments, fund transfers, and mobile credit purchases. This study aims to examine the role of POSPAY in enhancing operational efficiency, customer convenience, and access to financial services to support national financial inclusion. A qualitative descriptive method was employed through library research using secondary data. The findings indicate that POSPAY has a positive impact on the company’s revenue, helps maintain competitiveness amid the growth of fintech companies, and extends service reach to frontier, outermost, and disadvantaged (3T) areas. Therefore, POSPAY serves as a strategic innovation in supporting financial service digitalization and strengthening PT Pos Indonesia’s position in the digital financial ecosystem.